2017
DOI: 10.1083/jcb.201611057
|View full text |Cite
|
Sign up to set email alerts
|

Bipotent progenitors as embryonic origin of retinal stem cells

Abstract: Retinal stem cells yield all retinal cell types, but their embryonic origin is elusive. Using a Zebrabow-based clonal analysis and in vivo lineage analyses, Tang et al. identify bipotent progenitors as the cell of origin of retinal stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 87 publications
2
36
0
Order By: Relevance
“…Nevertheless, terminating clones arising from the very periphery of the niche unambiguously demonstrate that some stem cells failed to self-renew throughout the life of the animal. Moreover, our finding that only cells in the first two rows of the CMZ have stem cell potential is consistent with in vivo time-lapse data (Wan et al , 2016; Tang et al , 2017). Interestingly, retrograde movement of row 2 cells into row 1 of the CMZ occurs in vivo (Wan et al , 2016), which we also observed in our simulations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, terminating clones arising from the very periphery of the niche unambiguously demonstrate that some stem cells failed to self-renew throughout the life of the animal. Moreover, our finding that only cells in the first two rows of the CMZ have stem cell potential is consistent with in vivo time-lapse data (Wan et al , 2016; Tang et al , 2017). Interestingly, retrograde movement of row 2 cells into row 1 of the CMZ occurs in vivo (Wan et al , 2016), which we also observed in our simulations.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo , the spatial extent of the CMZ stem cell domain is believed to be defined by cues such as nearby blood vessels (Wan et al , 2016; Tang et al , 2017). Therefore, we defined the virtual stem cell domain with a fixed size of 25 μm, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same might be true for retinal stem cells as well. In addition, rare dormant cells have recently been described at the extreme tip of the zebrafish CMZ (Tang et al 2017), suggesting that the Xenopus retinal stem cell cohort might be composed of both "activated" proliferating cells and "resting" quiescent ones, as shown in neurogenic zones of the adult mammalian or zebrafish brain (Than-Trong and Bally-Cuif 2015; Chaker et al 2016). Finally, our personal observations suggest that the dorsal and ventral parts of the CMZ do not proliferate at the same rate, indicating an additional regional heterogeneity in cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%